Environmental Education in Vietnam: A Critical Discourse Analysis - Pham, Tien (Comparative and International Education / Éducation comparée et internationale, 2023)
This article utilizes critical discourse analysis to investigate the environmental education (EE) policy in Vietnam by analyzing seven policy documents. It examines the language used in the policy papers and underlying factors that shape the policy, including power relations, ideologies, and sociopolitical influences. The findings reveal a lack of shared understanding of EE and the neglect of its social aspect, leading to limited integration of EE content in national curricula and the prevalence of performative language within the policy. This undervaluation of EE can be attributed to the influence of Confucianism and the traditional education model inherited from the former Soviet Union. It also suggests that the present policy predominantly reflects the ideologies and priorities of the ruling class, who prioritizes economic growth over sustainability. This study underscores the need for a nuanced approach in policymaking that integrates sociocultural dimensions and addresses the performative gap in environmental education, paving the way for more effective and context-sensitive strategies in Vietnam’s response to educational challenges posed by climate change.